Identification of Candidate Proteins Binding to Prion Protein - Fruma Yehiely (Neurobiology of Disease, 1997)
Prion diseases are disorders of protein conformation that produce neurodegeneration in humans and animals. Studies of transgenic (Tg) mice indicate that a factor designated protein X is involved in the conversion of the normal cellular prion protein (PrPC) into the scrapie isoform (PrPSc); protein X appears to interact with PrPCbut not with PrPSc. To search for PrPCbinding proteins, we fused PrP with alkaline phosphatase (AP) to produce a soluble, secreted probe. PrP–AP was used to screen a λgt11 mouse brain cDNA library, and six clones were isolated. Four cDNAs are novel while two clones are fragments of Nrf2 (NF-E2 related factor 2) transcription factor and Aplp1 (amyloid precursor-like protein 1). The observation that PrP binds to a member of the APP (amyloid precursor protein) gene family is intriguing, in light of possible relevance to Alzheimer's disease. Four of the isolated clones are expressed preferentially in the mouse brain and encode a similar motif.